A rare case of wandering spleen with its unreported associations: case report and literature review - Digumarthi, Asha R.; Khanna, Seema; Satendra Kumar; Sanjeev K. Gupta (International Surgery Journal, 2023)
Wandering spleen (WS) is a rare clinical entity with unclear clinical picture. Patient can be asymptomatic or can present with acute abdomen, based on the degree of associated splenic torsion, but most of the cases needed an emergency splenectomy. We herein report an unusual presentation of a wandering spleen in the elderly with thrombocytosis, portal, and splenic vein thrombosis, and sinistral hypertension. To the best of our knowledge, this is the first case report documenting all these associations altogether. This case report describes how this challenging case was managed well. Splenectomy was inevitable in this patient as the spleen was infarcted. This enlightens the need for timely diagnosis and intervention of wandering spleen for splenic preservation.